Housinganywhere.com (b) - Ghahvechi, Arefeh, (SAGE Knowledge. Cases., 2017)
International growth should be at the heart of our strategies now, said Niels van Deuren, CEO of HousingAnywhere.com, a so-called online housing rental site founded in 2009 that connected "searchers" individuals looking for short-term accommodation with "suppliers" students offering housing. Universities, being the sole clients of HousingAnywhere's services, were the ones picking up the bill to ensure that their incoming students had accommodation upon arrival in the country. HousingAnywhere had thrived in the marketplace by creating a platform that helped resolve the seemingly obstinate problem of both finding and leasing short-term accommodation in an international context. By the summer of 2014, 91 universities across 13 different countries signed contracts with HousingAnywhere, and the company was beginning to operate on a global scale.In spite of its initial success, HousingAnywhere had been facing some difficulties. Insufficient user marketing had led to a drop in the number of rooms supplied and clients were beginning to discontinue their contracts with HousingAnywhere. Significant strategic initiatives were undertaken to revive the business, but despite their impact, Niels knew that for a company like HousingAnywhere, further growth was necessary otherwise the business would become obsolete. In achieving this goal, Niels was in need of additional financing.